Compression of neonatal raised hemangioma. Indication and practical guide lines. - Mazzotta, F.; Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Neonatal raised angioma undergoes spontaneous regression in most cases. Therefore, whatever therapeutical approach should face this reality. In this report are considered the advantages and side effects of compression treatment. Moreover, some guide lines for the latter are suggested.